The Place for Research in Counsellors’ Education - Fahmy, Pauline (Canadian Journal of Counselling and Psychotherapy, 2011)
A distinction is maintained in most universities which offer graduate studies in counselling, between professional and research degrees, both at the masters and doctorate levels. This distinction is related to two widespread misconceptions concerning: 1) what being a professional in the human sciences field means; 2) what is or should be considered as research in this field. The author contends that counsellors cannot avoid being researchers and thus being trained as such because of the research activity basically involved in their activity as practitioners. Counsellor educators are confronted with the task of offering new and more adequate models and methodologies for researchers relevant to their specific field.